Statistical characterization of actigraphy data during sleep and wakefulness states - Adamec, Ondřej; Domingues, Alexandre; Paiva, Teresa; Sanches, J. Miguel (Conference proceedings ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2010)
Human activity can be measured with actimetry sensors used by the subjects in several locations such as the wrists or legs. Actigraphy data is used in different contexts such as sports training or tele-medicine monitoring. In the diagnosis of sleep disorders, the actimetry sensor, which is basically a 3D axis accelerometer, is used by the patient in the non dominant wrist typically during an entire week. In this paper the actigraphy data is described by a weighted mixture of two distributions where the weight evolves along the day according to the patient circadian cycle. Thus, one of the distributions is mainly associated with the wakefulness state while the other is associated with the sleep state. Actigraphy data, acquired from 20 healthy patients and manually segmented by trained technicians, is used to characterize the acceleration magnitude during sleep and wakefulness states. Several mixture combinations are tested and statistically validated with conformity measures. It is shown that both distributions can co-exist at a certain time with varying importance along the circadian cycle.
Keywords: aktigrafie; Equipment Design; bdění; Telemedicine; Models, Statistical; Wakefulness; monitorování fyziologických funkcí; Monitoring, Physiologic; Computer Communication Networks; časové faktory; Time Factors; lidé; statistické modely; Circadian Rhythm; telemedicína; cirkadiánní rytmus; Actigraphy; spánek; Sleep; design vybavení; počítačové komunikační sítě; Humans